ANALISIS KEPEMILIKAN MANAJERIAL, UKURAN PERUSAHAAN, DAN PROFITABILITAS YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN (STUDI PADA PERUSAHAAN MANUFAKTUR SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2016) - Megaretta, Verorina; Panjaitan, Fery; Hariyani (Jurnal Akuntansi Bisnis Dan Keuangan, 2018)
This thesis which is written by Verorina Megaretta, with student identification number 540140002 entitled "Managerial Ownership Analysis, Company Size, and Profitability Affecting Timeliness of Financial Reporting (Study on Food and Beverage Sector Manufacturing Companies Listed on Indonesia Stock Exchange 2012-2016 ) ". This study aims to determine Managerial Ownership, Company Size, and Profitability Affect the Timeliness of Financial Reporting in Manufacturing Companies Food and Beverage Sectors Listed on Indonesia Stock Exchange. The data collection method used is the data analysis method. Data that are used are in the form of financial statements of food and beverage manufacturing companies that have been audited from 2012-2016. This research uses multiple linear regression analysis methods. As a tool spss 22 program is used for processing statistical data. The results show that managerial ownership and firm size have no significant effect on the timeliness of financial reporting while profitability has a significant effect on the timeliness of financial reporting. Managerial ownership has no significant effect 4,440E-5 with a significant level of 0,117 to the timeliness of financial reporting, firm size does not have a significant effect value of 0,006 with a significant level of 0,598 to the timeliness of financial reporting, profitability has a significant value 2,215 with significant level 0,001 to the timeliness of financial reporting and managerial ownership, firm size, profitability has a significant effect on the timeliness of financial reporting simultaneously. Based on the calculation Fcount 4,810 is bigger than Ftable 2,79 with a significant level of 0,005. The value of the Determination Coefficient in the regression model is 0,221. This value indicates that the variable ability of Managerial Ownership, Company Size, and Profitability in explaining the variable of Timeliness of Financial Reporting is equal to 22,1% while the rest is equal to 77,9% because to other factors such as company age, leverage, liquidity, and hood’s reputation.